MARKET INDICATORS OF CHARUTINHO (Hemiodus spp.) PICKLE - Luiz Monteiro dos Santos Junior; Bruno Kaleb dos Santos Almeida; Paulo Roberto Brasil Santos; Hérlon Mota Atayde (Instituto Federal de Educação, Ciência e Tecnologia do Piauí, 2024)
Fresh samples of charutinho (Hemiodus spp.) were used to prepare four fish pickles formulations: F1 = 55v4s, F2 = 55v5s, F3 = 45v4s e F4 = 45v5s), which differ in the percentual content of alcohol vinegar and common iodized salt, indicated by numbers before the letters "v" and "s" of formulations code. They were analyzed by 78 untrained judges as following indicators and hedonic scale: acceptability (seven points), purchase intention (five points), and consumption frequency (mixed scale). Mostly, the judges accepted the formulations with minor vinegar content (F3 and F4).  Of them, that with more salt content had the highest average.  This same formulation has the best notes as purchase intention and consumption frequency. The charutinho pickle showed promising results by market indicators. The formulation with minor vinegar and more salt is better for entrepreneurial initiatives.